TIPOLOGI WACANA MOP ‘HUMOR’ DALAM MASYARAKAT PAPUA: IDENTIFIKASI DAN EKSPLORASI - Hugo Warami (Balai Bahasa Provinsi Papua, 2019)
This article aims to describe the discourse joke by Papuans called Mop. Mop 'joke' discourse is one of the collective wealth of the people of Papua sastra inherited from generation to generation. Mop 'joke' discourse contains elements of humor or wit; the creation of a civilized beings. Mop 'joke' discourse has the potential of complex linguistic and supported by certain persuasive power that humorous effect, can be entertaining, pleasing, reduce tasa tense and unhappy audience. This article is an attempt to identify and explore initial typology forms of discourse in society Mop Papua with projecting typology that includes: (i) the story, (ii) conversation or dialogue, (iii) puzzles, and (iv) poetry.